Year‐Round In Situ Measurements of Arctic Low‐Level Clouds: Microphysical Properties and Their Relationships With Aerosols. Issue 3 (15th February 2019) - Koike, M.; Ukita, J.; Ström, J.; Tunved, P.; Shiobara, M.; Vitale, V.; Lupi, A.; Baumgardner, D.; Ritter, C.; Hermansen, O.; Yamada, K.; Pedersen, C. A.
Abstract: Two years of continuous in situ measurements of Arctic low‐level clouds have been made at the Mount Zeppelin Observatory (78°56′N, 11°53′E), in Ny‐Ålesund, Spitsbergen. The monthly median value of the cloud particle number concentration ( N c ) showed a clear seasonal variation: Its maximum appeared in May–July (65 ± 8 cm −3 ), and it remained low between October and March (8 ± 7 cm −3 ). At temperatures warmer than 0 °C, a clear correlation was found between the hourly N c values and the number concentrations of aerosols with dry diameters larger than 70 nm ( N 70 ), which are proxies for cloud condensation nuclei (CCN). When clouds were detected at temperatures colder than 0 °C, some of the data followed the summertime N c to N 70 relationship, while other data showed systematically lower N c values. The lidar‐derived depolarization ratios suggested that the former (CCN‐controlled) and latter (CCN‐uncontrolled) data generally corresponded to clouds consisting of supercooled water droplets and those containing ice particles, respectively. The CCN‐controlled data persistently appeared throughout the year at Zeppelin. The aerosol‐cloud interaction index (ACI = dln N c /(3dln N 70 )) for the CCN‐controlled data showed high sensitivities to aerosols both in the summer (clean air) and winter–spring (Arctic haze) seasons (0.22 ± 0.03 and 0.25 ± 0.02, respectively). The air parcel model calculations generally reproduced these values. The threshold diameters of aerosol activation ( D act ), which account for the N c of the CCN‐controlled data, were as low as 30–50 nm when N 70 was less than 30 cm −3, suggesting that new particle formation can affect Arctic cloud microphysics. Key Points: Two years of in situ measurements of the number concentrations of Arctic cloud particles ( N c ) show a clear seasonal variation with a maximum in summer Aerosols with diameters as small as 30 nm likely serve as cloud condensation nuclei (CCN) due to the low CCN concentrations in the Arctic The aerosol‐cloud interaction (ACI) index for CCN‐controlled clouds was estimated to be approximately 0.22, and it does not show a clear seasonal variation